Il sistema contabile e la struttura di gobernó del “Campansi” nella seconda metà dell'ottocento - Giuseppe Catturi; Daniela Sorrentino (De Computis, 2017)
In every city community, there always exist social, economic and political- administrative bodies, whose activities and organisational structures delineate and convey the historical and cultural periods experienced by that community. The city community we aim at investigating is the Sienese one. Siena is universally recognised for its medieval reminders, as well as for those of the Renaissance, distinctly appreciable in its current urban patterns, painting pieces, and cultural goods, of which it is plenty and rightly proud. The organisation we identified as one traditionally characterising –at least in the last century and a half- and still characterising the Sienese history and culture, is the Ricovero di Mendicità, later named Casa di riposo in Campansi per anziani, unanimously known as “Campansi”. Undoubtedly, the Campansi one is not the only institution whose structural and operational evolution contributed – and keeps on contributing- to shape the history of Siena, from the social, political and institutional points of view. Nevertheless, it is surely one of the most peculiar ones, in that it has been involved in those charitable activities, which exalted Siena since the second millennium, at the time of the restoring and propitiatory journeys to the main religious destinations: Rome, Jerusalem, and Saint James of Compostela. In this study we adopt a business administration perspective, with particular reference to the structure of the accounting system and its related documentation, which the organisation had been producing in order to memorise, summarise and communicate its administrative events, these latter occurring from the exercise of its institutional function. Moreover, we acknowledge the related governance structure, selected with the purpose of making operational decisions, verifying their execution, and controlling the deriving effects. As a matter of fact, there is a tight interdependency between the governance structure and the accounting system of whichever organisation. Particularly, the investigation refers to the period we considered the most significant and interesting, the one comprised between the issuing of the law “Sull'Amministrazione delle Opere pie” (3rd August 1862) and law “Istituzioni pubbliche di beneficenza”, in 1890, respectively known as Rattazzi and Crispi law, from the Prime Ministers in charge at the time of their enactment.